Long-Term Hearing Outcomes following Total Ossicular Reconstruction with Titanium Prostheses. (July 2019) - Wood, C. Burton; Yawn, Robert; Lowery, Anne Sun; O'Connell, Brendan P.; Haynes, David; Wanna, George B.
Objective: (1) Characterize a large cohort of patients undergoing total ossicular chain reconstruction with titanium prosthesis. (2) Analyze long-term hearing outcomes of the same cohort. Study Design: Case series with chart review. Setting: Tertiary care center. Subject and Methods: This study reviews patients who underwent total ossicular chain reconstruction (OCR) with titanium prostheses (TORPs) at a single tertiary care center from 2005 to 2015. Patient charts were reviewed for demographic data, diagnosis, and operative details. Patients were included in statistical analysis if length of follow-up was 2 years or more. Evaluation of hearing improvement was made by comparing preoperative air-bone gap (ABG) and ABG at follow-up at 2 years. Results: In total, 153 patients were identified who met inclusion criteria. The mean age of included patients was 40 years (range, 6-89 years). Sixty patients (39%) had a history of OCR, and 120 patients (78%) had a diagnosis of cholesteatoma at the time of OCR. Preoperatively, the mean ABG was 36 ± 12, whereas the mean ABG at 2-year follow-up improved to 26 ± 13. This was statistically significant ( P < .0001) using a Wilcoxon matched-pairs signed rank test. Twelve patients (8%) required revision OCR. Two revisions were performed due to prosthesis extrusion (<1%). Conclusion: Titanium prostheses lead to significant improvement in hearing over long periods. The results are sustained as far out as 5 years following surgery. In addition, rates of revision surgery with titanium TORPs are low. Based on this series, there are no readily identifiable predictors for outcomes following total OCR.